SUGARCANE LAND USE AND WATER RESOURCES ASSESSMENT IN GAGARAWA LGA, JIGAWA STATE, NIGERIA - Tudunwada, I. Y; Maina, M. M. (FUDMA Journal of Earth and Environmental Sciences, 2024)
The availability of water resources for sugarcane production in Gagarawa, Jigawa State, Nigeria, a potential area for large-scale sugarcane production, was assessed. Sugarcane (Saccharum officinarum L.), a tall perennial grass belonging to the grass family Gramineae, is a long-duration crop that produces enormous amounts of biomass. It is the major crop from which sugar is produced. With Nigeria’s growing population, demand for sugar is rising, but production is low. Water resources are key to producing sugarcane. Many areas in northern Nigeria may be suitable for sugarcane, except for water availability. Remote sensing data from Landsat 7.0 and STRM 30m were used to analyse the physical land qualities. Annual rainfall (500mm) and evaporation (73.1 mm/day) were obtained from GIOVANNI & Power LARC. Infiltration and silt sedimentation were determined using soil infiltration test and siltation from runoff silt content (204mm/hr). Sugarcane water requirements and groundwater were determined using CropWat model 8. The analysis indicated that the land is perfect for rainfed and irrigated sugarcane cultivation, with an average annual rainfall of 500 mm. Sugarcane requires 2088 mm of water, resulting in a deficit of 1588 mm, which is to be supplemented by irrigation. Groundwater potential of 1239.4 mm was available but still indicates a deficit. Alternative sources to compensate for the deficit are River Hadejia and the field's construction of rainwater harvesting structures. The recommendation was to consider using surface and groundwater conservation in addition to the annual rainfall in the study area.